Recent Advances on Nanoparticle Based Strategies for Improving Carotenoid Stability and Biological Activity - Kandi Sridhar; Baskaran Stephen Inbaraj; Bing-Huei Chen (MDPI AG, 2021)
Carotenoids are natural pigments widely used in food industries due to their health-promoting properties. However, the presence of long-chain conjugated double bonds are responsible for chemical instability, poor water solubility, low bioavailability and high susceptibility to oxidation. The application of a nanoencapsulation technique has thus become a vital means to enhance stability of carotenoids under physiological conditions due to their small particle size, high aqueous solubility and improved bioavailability. This review intends to overview the advances in preparation, characterization, biocompatibility and application of nanocarotenoids reported in research/review papers published in peer-reviewed journals over the last five years. More specifically, nanocarotenoids were prepared from both carotenoid extracts and standards by employing various preparation techniques to yield different nanostructures including nanoemulsions, nanoliposomes, polymeric/biopolymeric nanoparticles, solid lipid nanoparticles, nanostructured lipid nanoparticles, supercritical fluid-based nanoparticles and metal/metal oxide nanoparticles. Stability studies involved evaluation of physical stability and/or chemical stability under different storage conditions and heating temperatures for varied lengths of time, while the release behavior and bioaccessibility were determined by various in vitro digestion and absorption models as well as bioavailability through elucidating pharmacokinetics in an animal model. Moreover, application of nanocarotenoids for various biological applications including antioxidant, anticancer, antibacterial, antiaging, cosmetics, diabetic wound healing and hepatic steatosis were summarized.